(untitled) (El Taco en la Brea, 2025)
This article aims to present the results of the research project «Teaching Practices in the Instruction of Argentine Literature», which led to the award of the Master’s degree in Teaching Language and Literature in 2023. The research focused on understanding how teaching practices unfolded in the instruction of Argentine literature texts offered in the classes of the fifth and sixth years of the Oriented Superior Cycle of Secondary Education in the city of Formosa. To achieve this, a study of six particular cases of teaching practices was conducted based on variables such as criteria for selecting the corpus of texts, proposed reading modes, the teacher’s trajectory, and the school institution in which they operate. From there, it was possible to interpret their implicit theories about the teaching of Argentine literature.